Lean fish consumption is associated with lower risk of metabolic syndrome: a Norwegian cross sectional study - C. Tørris; M. Molin; M. Småstuen Cvancarova (BMC Public Health, 2016)
Abstract Background Fish consumption may have a role in reducing the prevalence of metabolic syndrome (MetS). The aim of this study was to identify associations between fish consumption and MetS and its components, especially regarding differences concerning consumption of fatty and lean fish. Methods This cross sectional study uses data from the Tromsø 6 survey (2007–08), where a sample of 12 981 adults, aged 30–87 years (47 % men) from the Norwegian general population was included. Fish consumption was assessed using food frequency questionnaires (FFQ). Blood sample assessments, anthropometric and blood pressure measurements were carried out according to standard protocols. MetS was defined using the Joint Interim Societies (JIS) definition. All tests were two-sided. Analyses were performed using IBM SPSS Statistics 22 (Pearson’s correlation, Chi-Square tests, analysis of variance (ANOVA), linear and logistic regression models). Results Mean age was 57.5, and the prevalence of MetS was 22.6 %. Fish consumption once a week or more was associated with lower risk of having MetS among men (OR 0.85, CI 95 % 0.74 to 0.98, P = 0.03). In the adjusted models, lean fish consumption was associated with a decreased risk of having MetS, whereas fatty fish consumption was not associated with a decreased risk of having MetS. Both an increased fatty and lean fish consumption (0–1 times per month, 2–3 times per month, 1–3 times per week, 4–6 times per week, 1–2 times per day) were associated with decreased serum triglyceride (TG), and increased high-density lipoprotein cholesterol (HDL-C). Conclusions Fish consumption may be associated with a lower risk of having MetS and consumption of lean fish seems to be driving the association. Further investigation is warranted to establish associations between fish consumption and MetS.